Solvothermal Synthesis of Magnetic CoFe2O4/Carbon Nanocomposites with Superior Visible Light Photocatalysis - Shi, Dongyang (Langmuir : the ACS journal of surfaces and colloids, 2025)
In order to enhance the photocatalytic performance of CoFe2O4, carbon (C) was exploited to modify it through developing a CoFe2O4/C heterojunction photocatalyst. CoFe2O4/C nanocomposites with varying C contents were fabricated through a simple one-pot solvothermal approach by adjusting the dosage of glucose. The photocatalytic capabilities of the as-prepared CoFe2O4/C nanocomposites were evaluated by the reduction of Cr(VI) under visible light exposure. The experimental results indicated that all of the as-prepared CoFe2O4/C products had substantially greater photocatalytic Cr(VI) reduction activity than CoFe2O4, with CoFe2O4/C-2 being the optimal photocatalyst. CoFe2O4/C-2 not only showed a photocatalytic activity 6.7 times greater than that of CoFe2O4, but it also outperformed a considerable number of previously reported visible light photocatalysts. Furthermore, the appropriate optimization of the photocatalytic experiment parameters could further improve the photocatalytic Cr(VI) reduction rate of CoFe2O4/C-2. In addition, CoFe2O4/C-2 also exhibited superior photocatalytic stability. Another advantageous feature of CoFe2O4/C-2 is its easy recoverability from water through a simple magnetic attraction. The remarkably enhanced photocatalytic activity of CoFe2O4/C-2 is primarily ascribed to the improved separation and transfer of photogenerated charges, which is a result of its p-n heterojunction structure. This study offers a valuable reference for the synthesis and application of a highly efficient magnetic CoFe2O4/C photocatalyst for treating Cr(VI) contamination in water bodies